Characterization of a Family With c9FTD/ALS Associated With the GGGGCC Repeat Expansion in C9ORF72 - Savica, Rodolfo (2012)
BACKGROUND: The hexanucleotide repeat in the chromosome 9 open reading frame 72 (C9ORF72) gene was recently discovered as the pathogenic mechanism underlying many families with frontotemporal dementia (FTD) and/or amyotrophic lateral sclerosis (ALS) linked to chromosome 9 (c9FTD/ALS). We report the clinical, neuropsychological, and neuroimaging findings of a family with the C9ORF72 mutation and clinical diagnoses bridging the FTD, parkinsonism and ALS spectrum. OBJECTIVE: To characterize the antemortem characteristics of a family with c9FTD/ALS associated with the GGGGCC repeat expansion in C9ORF72 DESIGN: Clinical series. SETTING: Tertiary care academic medical center. PATIENTS: The members of the family affected by the mutation with features of FTD and/or ALS. MAIN OUTCOME MEASURES: Clinical, neuropsychological, and neuroimaging assessments. RESULTS: All three examined subjects had the hexanucleotide expansion detected in C9ORF72. All had personality/behavioral changes early in the course of the disease. One case had levodopa-unresponsive parkinsonism, and one had ALS. MRI showed symmetric bilateral frontal, temporal, insular and cingulate atrophy. CONCLUSIONS: This report highlights the clinical and neuroimaging characteristics of a family with c9FTD/ALS. Further studies are needed to better understand the phenotypical variability and the clinico-neuroimaging-neuropathologic correlations.